A Serious Game for Socioemotional Assessment Suitable for Children - Kalomenconkovas, Igor F. M.; Matos, Simone N.; Torrens, Isabel C.; Borges, Helyane B. (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2025)
Socioemotional skills allow individuals to resolve conflicts and deal with emotions. These skills can be addressed in digital tools such as serious games. Introduction: Serious games have the potential to enhance players' cognitive abilities, as well as foster interpersonal and intrapersonal improvements. Objective: To develop a serious game for children that assesses and promotes empathy in children aged 5 to 7 years old through interactive and reflective mechanics, using a Maieutic approach inspired by the Socratic method. Methodology: The research followed four main stages: (1) Conceptual Design, with definition of objectives and preparation of questionnaires; (2) Communication Design, focusing on interface and gameplay; (3) Structural Design, with definition of the system architecture; and (4) Development, implementation and validation Design. Results: The game developed seeks to evaluate cognitive and affective responses related to empathy, in addition to engaging children through interactive scenarios and a reward system.